Misstatement Direction, Litigation Risk, and Planned Audit Investment - Barron, Orie; Pratt, Jamie; Stice, James D. (Journal of Accounting Research, 2001)
This study reports the results of an experiment showing that auditor assessments of litigation risk and planned audit investments are higher when potential errors overstate financial performance than when those errors understate performance. This result is much stronger in the presence of high levels of litigation risk in the client’s industry. These results suggest that in industries where litigation risk is high audited financial statements may contain more unintentional material understatement errors than overstatement errors. Thus, litigation risk—through its effect on auditors—may encourage financial statements that understate firm performance